2010
DOI: 10.1111/j.1469-8137.2010.03482.x
|View full text |Cite
|
Sign up to set email alerts
|

The second face of a known player: Arabidopsis silencing suppressor AtXRN4 acts organ‐specifically

Abstract: Summary Plant viruses exploit the symplastic transport pathway provided by plasmodesmata by encoding for specialized movement proteins, which interact with host factors to enable viral intracellular and intercellular spread. Stable expression of the Potato leaf roll virus movement protein MP17 in Arabidopsis results in a carbohydrate export block and stunted growth. To identify host factors essential for viral infection, we screened a progeny population of EMS (ethyl methanesulfonate)‐mutagenized Arabidopsis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…In order to identify host factors essential for viral infection, seeds of Col‐16 were EMS‐mutagenized and M 2 individuals were phenotyped for reduction or loss of MP17:GFP fluorescence (see also File S1). A similar approach lead to identification of EXORIBONUCLEASE 4 (XRN4) (Vogel et al. , 2011), which was previously described as a suppressor of gene silencing in Arabidopsis (Gazzani et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to identify host factors essential for viral infection, seeds of Col‐16 were EMS‐mutagenized and M 2 individuals were phenotyped for reduction or loss of MP17:GFP fluorescence (see also File S1). A similar approach lead to identification of EXORIBONUCLEASE 4 (XRN4) (Vogel et al. , 2011), which was previously described as a suppressor of gene silencing in Arabidopsis (Gazzani et al.…”
Section: Resultsmentioning
confidence: 99%
“…As it has been reported that uncapped mRNA accumulates in xrn4 mutants (Gazzani et al. , 2004), we also tested the previously described 12‐1‐1/xrn4/MP17:GFP mutant (Vogel et al. , 2011).…”
Section: Resultsmentioning
confidence: 99%
“…One of the phenotypes of the xrn4 mutants is higher levels of RNA silencing (Gazzani et al 2004). Indeed, xrn4 mutants in Arabidopsis are less susceptible to infection by cauliflower mosaic virus and turnip mosaic virus due to gene silencing of viral genes (Gy et al 2007;Vogel et al 2010). One possibility is that the down set is decreased in xrn4 due to the production of secondary siRNA generated from their uncapped transcripts and subsequent siRNA-mediated decay.…”
Section: Stamen Association Of Transcripts That Decrease In Xrn4 Mutantsmentioning
confidence: 99%
“…In plants, the decapping machinery includes the decapping enzyme DCP2 and its activators DCP1, DCP5, VARICOSE (VCS) (Deyholos et al , ; Xu et al , ; Goeres et al , ; Brodersen et al , ; Xu & Chua, , ; Motomura et al , ) as well as the exoribonuclease XRN4 (Olmedo et al , ; Potuschak et al , ; Gregory et al , ; Rymarquis et al , ; Vogel et al , ). It is thought that DCP1, DHH1 and DCP5 form mRNPs for translational repression of target mRNA, which are then subject to decapping by recruitment of DCP2 and VCS and digestion by XRN4 (Xu & Chua, , ).…”
Section: Introductionmentioning
confidence: 99%